Developmental changes in executive functions during adolescence: A study of inhibition, shifting, and working memory - Theodoraki, Thalia E.; McGeown, Sarah P.; Rhodes, Sinead M.; MacPherson, Sarah E. (British journal of developmental psychology, 2020)
The development of executive functions (EFs) has primarily been studied among younger children, despite research suggesting that particular aspects of EFs continue to develop throughout adolescence and into adulthood. This study investigated whether EFs continue to develop during the later stages of adolescence: three related, yet separable EF components – inhibition, shifting, and working memory – were examined in a cross‐sectional sample of 347 adolescents (aged 14–18 years). After adjusting for covariates, age was found to be a significant predictor of pupils’ performance on the inhibition but not the shifting or working memory tasks, suggesting different developmental trajectories for the three EF components. Controlling for non‐executive processes implicated in performing the inhibition and working memory tasks had the most pronounced effect on the relationship between performance on those tasks and age. Finally, socioeconomic status was a significant predictor of performance on all tasks. Implications for research and practice are discussed. Statement of contribution What is already known on this subject? Brain regions associated with EFs continue to mature throughout adolescence, implying ongoing development of EFs. Behavioural studies demonstrate that certain EFs have not yet reached their adult levels in early adolescence. What the present study adds Changes in inhibition, but not shifting or working memory task performance, are evident among older adolescents. Lower‐order processes tapped by EF tasks act as confounds in the relationship between age and task performance. Socioeconomic status is a significant predictor of adolescents’ performance on EF tasks.